Twin Reversed Arterial Perfusion Sequence (TRAPS): A Case Report - Astari, Prilly; Efendi Lukas (Faculty of Medicine, Hasanuddin University., 2024)
Introduction and importance: Acardiac twins are a complication of monozygotic twin pregnancies. Twin Reversed Arterial Perfusion Sequence (TRAPS) is reported to occur in approximately 1% of monochorionic twin pregnancies and 1 in 35,000 pregnancies. The objective is to provide a brief description of acardiac twins. Presentation of case: A 25-year-old multigravida, 35/36 weeks of twin pregnancy. On ultrasound examination of acardiac twins, no heart structure, head bones, and sternum were found, and the shape of the fetus was unclear. Vaginal delivery was carried out; the first live female baby was born, followed by the acardiac baby. The acardiac baby is seen to have imperfect development of the head and upper extremities, Spina bifida, deformity of the lower extremities, Phocomelia of the lower limb, and Split foot. After 9 days, the baby's condition improved, and she was allowed to go home. Discussion: TRAPS's etiology and pathophysiological mechanisms are still poorly understood. Ultrasound findings show an absent or non-functioning heart in one twin, malformation with cystic hygroma, and generalized edema. The first baby (donor twin) was born prematurely, weighing 2200 grams, and there were no signs of heart failure, while the second baby (acardiac) was born weighing 1050 grams. Current therapy for acardiac twins aims to prevent congestive heart failure in the donor twin and stop blood flow to the acardiac twin. Conclusions: Early diagnosis of abnormalities in monochorionic pregnancy using ultrasound in the first trimester plays a role in assessing the prognosis for the viability of the pregnancy.